Ion-pair Formation for the Determination of Mianserin Using Fast Sulphon Black F - Ratnakaram, Dr. Venkata Nadh (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The objective of the current study is to develop a colorimetric method for the determination of mianserin, an antidepressant drug. Materials and Methods: Fast Sulphon Black F, an acidic dye was used to develop a soluble colored ion-pair complex. The complex was extracted into an organic solvent and absorbance was measured. Results: Reaction conditions were optimized to obtain a sensitive and stable chromophore (λmax 554 nm) in dichloromethane. Good linearity was observed for the calibration curve plotted in the studied concentration range (4–14 μg/mL) with regression analysis (r > 0.9997). High percentage recovery values (98.25–101.40) show that the method is accurate. Reproducibility of the method is evident from lower relative standard deviation (<2%) for both intra- and inter-day precision studies. Conclusions: The proposed method is validated as per the existing ICH guidelines. This method is simple as it does not require any pre-treatment process.